Global reach of over 20 years of experience in the patient-centered Fabry Registry: Advancement of Fabry disease expertise and dissemination of real-world evidence to the Fabry community - Wanner, Christoph; Ortiz, Alberto; Wilcox, William R; Hopkin, Robert J; Johnson, Jack; Ponce, Elvira; Ebels, Johan T; Batista, Julie L; Maski, Manish; Politei, Juan M; Martins, Ana Maria; Banikazemi, Maryam; et al. (Molecular genetics and metabolism, 2023)
Fabry disease (FD, α-galactosidase A deficiency) is a rare, progressive, complex lysosomal storage disorder affecting multiple organ systems with a diverse spectrum of clinical phenotypes, particularly among female patients. Knowledge of its clinical course was still limited in 2001 when FD-specific therapies first became available and the Fabry Registry (NCT00196742; sponsor: Sanofi) was initiated as a global observational study. The Fabry Registry has now been operational for over 20 years, overseen by expert Boards of Advisors, and has collected real-world demographic and longitudinal clinical data from more than 8000 individuals with FD. Leveraging the accumulating evidence base, multidisciplinary collaborations have resulted in the creation of 32 peer-reviewed scientific publications, which have contributed to the greatly expanded knowledge on the onset and progression of FD, its clinical management, the role of sex and genetics, the outcomes of enzyme replacement therapy with agalsidase beta, and prognostic factors. We review how the Fabry Registry has evolved from its inception to become the largest global source of real-world FD patient data, and how the generated scientific evidence has helped to better inform the medical community, individuals living with FD, patient organizations, and other stakeholders. The patient-centered Fabry Registry fosters collaborative research partnerships with the overarching goal of optimizing the clinical management of patients with FD and is well positioned to add to its past achievements.
Keywords: pozorovací studie jako téma; Observational Studies as Topic; alfa-galaktosidasa; Patient-Centered Care; real-world data; enzymová substituční terapie; Phenotype; Humans; enzyme replacement therapy; Registry; alpha-Galactosidase; Fabry disease; Female; Registries; agalsidase beta; ženské pohlaví; natural history; Enzyme Replacement Therapy; Fabry Disease; registrace; péče orientovaná na pacienta; lidé; fenotyp; Fabryho nemoc